2019
DOI: 10.3390/ani9100757
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of a Standardized Qualitative Behaviour Assessment and Exploration of Potential Influencing Factors on the Emotional State of Dairy Calves

Abstract: Simple SummaryAlthough welfare states of dairy calves are of public and scientific concern, no standardized protocol exists to assess the emotionality of these animals. Therefore, this study aimed at investigating and establishing a calf-specific term list for Qualitative Behavior Assessment (QBA), a technique that is already validated for assessing emotional states in many animal species. The statistically supported results showed that agreement can be reached among observers, terms showed varied results acro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 25 publications
1
9
0
Order By: Relevance
“…Studies applying standardized welfare assessment protocols to dual-purpose chickens are rarely found [46]. Using the QBA as a reliable holistic methodology to rate the animals' emotional health is supported, for example, by studies on calves [47] and sick and recovering dairy cows [48], and has also been queried by others, e.g., based on the feasibility and reliability of the assessment protocol for pigs [49,50]. Recently, the QBA was also applied for the assessment of broiler [21] and layer welfare [51].…”
Section: Discussionmentioning
confidence: 99%
“…Studies applying standardized welfare assessment protocols to dual-purpose chickens are rarely found [46]. Using the QBA as a reliable holistic methodology to rate the animals' emotional health is supported, for example, by studies on calves [47] and sick and recovering dairy cows [48], and has also been queried by others, e.g., based on the feasibility and reliability of the assessment protocol for pigs [49,50]. Recently, the QBA was also applied for the assessment of broiler [21] and layer welfare [51].…”
Section: Discussionmentioning
confidence: 99%
“…The QBA methodology was originally designed and validated around live assessments, where the assessor is directly watching the animals in situ ( 9 ). Since its inception, several studies have used video recordings for QBA ( 11 , 13 , 14 , 17 , 18 , 21 , 22 ). Research has indicated that video QBA (V-QBA) results correlate with other welfare indicators ( 17 , 18 ).…”
Section: Introductionmentioning
confidence: 99%
“…Two of the reviewed protocols applied QBA, with 20 and 21 terms used by the Welfare Quality ® and AWIN protocols, respectively. The definition of QBA terms used were modified from these protocols in combination with additional studies [29,35,36].…”
Section: Methodsmentioning
confidence: 99%